(untitled) (Scottish Historical and Archaeological Internet Reports, 2003)
The specific origin of the midden organic horizons remains an enigma and the pollen analytical data prompt more questions than answers. Of the possible origins only an origin from animal faeces can be discounted. Moreover, the presence of a relatively wide variety of pollen taxa can only be adequately explained by considering the exploitation of the most abundant habitats in North Uist, ie the machair grassland, peatland and moorland communities and possibly the cultivation of specific crops such as cereals. A combination of specific crops such as cereals. A combination of practices involving the exploitation of all the dominant habitats for thatching and/or animal bedding and/or fuel as well as the cultivation of specific crops would account for the pollen spectra of the Balelone midden organic horizons. It would not be unreasonable to suppose that the producers of the midden were indeed using such a wide variety of natural resources but there is no viable palaeoecological test which suggests itself as the panacea to this enigma.